SISTEM INFORMASI MANAJEMEN REACTIVE DAN PREVENTIVE MAINTENANCE MESIN PRODUKSI PADA PT.XYZ - Turnawajaya, Andri; Suharyanto, Cosmas Eko (Program Studi Sistem Informasi Institut Indobaru Nasional, 2024)
Maintenance is the job of keeping something in proper condition or the process of preserving a condition or situation. At PT.XYZ, the reactive process is still carried out manually, that is, if there is a problem with the production machine, the employees working on the production machine will notify the maintenance staff. The purpose of this study is to determine the process flow of reactive and preventive maintenance systems in damage management and maintenance of production machines at PT.XYZ, produce system designs, build systems and implement systems that have been built according to user requirements to solve reactive and preventive maintenance problems. . The method used in this research is observation technique and literature study. The results of this research are in the form of a web-based information system that is used to assist reactive and preventive maintenance processes so that they become more effective and efficient in the process of maintaining production machines.